2019
DOI: 10.1002/em.22326
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and Roadmap for Developing Panels of Hotspot Cancer Driver Gene Mutations as Biomarkers of Cancer Risk

Abstract: Cancer driver mutations (CDMs) are necessary and causal for carcinogenesis and have advantages as reporters of carcinogenic risk. However, little progress has been made toward developing measurements of CDMs as biomarkers for use in cancer risk assessment. Impediments for using a CDM‐based metric to inform cancer risk include the complexity and stochastic nature of carcinogenesis, technical difficulty in quantifying low‐frequency CDMs, and lack of established relationships between cancer driver mutant fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 156 publications
0
13
0
Order By: Relevance
“…Drugs and chemicals which are not mutagenic will not produce a signal in mutagenesis assays-either conventional or sequencing-based. However, as shown here, it appears possible to use ecNGS to infer carcinogenesis via detection of clonal expansions carrying oncogenic driver mutations as a marker of a neoplastic phenotype (43). This concept is more complex to design, insofar as it necessitates some a priori knowledge about the common drivers that are operative in different tissues in response to different classes of carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs and chemicals which are not mutagenic will not produce a signal in mutagenesis assays-either conventional or sequencing-based. However, as shown here, it appears possible to use ecNGS to infer carcinogenesis via detection of clonal expansions carrying oncogenic driver mutations as a marker of a neoplastic phenotype (43). This concept is more complex to design, insofar as it necessitates some a priori knowledge about the common drivers that are operative in different tissues in response to different classes of carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…Those which are not mutagenic would not produce a signal in conventional mutagenesis assays. We have shown that Duplex Sequencing, in addition to measuring mutagenesis, can also infer carcinogenesis via detection of clonal expansions carrying oncogenic driver mutations as a marker of a neoplastic phenotype 42 . We illustrated this phenomenon in response to a mutagenic chemical and follow-up efforts will be needed to demonstrate the same with non-genotoxic carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…SEER breast cancer incidence data was used to calculate a cumulative risk for each age (c), as the cumulative sum of incidence observed at the current and all previous years. Finally, the sum of PIK3CA and TP53 MFs ≥10 −4 in normal breast were plotted relative to the cumulative risk expected based on the tissue donor's age (d) magnitude of interindividual variability in CDMs is reflective of clonal expansion driven by CDMs in individuals, which occurs in a stochastic manner that mirrors the carcinogenic process itself (Harris et al, 2019). Another way to state this is that the more heterogeneity there is in normal tissue, the more potential there is for clonal selective advantage leading to carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…An approach that enables prediction of tumorigenic responses due to lifetime rodent exposures from shorter‐term rodent studies (28 days to 6 months) would be invaluable (Parsons 2018). Hotspot cancer driver mutations (hCDMs) have potential as biomarkers for use in carcinogenicity testing and assessing potential cancer risks associated with exogenous exposures, whether therapeutic, occupational, environmental, genotoxic, or non‐genotoxic (Harris et al ., 2019). Advantages of hCDMs as biomarkers of cancer risk include their relevance to carcinogenesis in both rodents and humans, their known roles in oncogenesis, and their ability to confer a growth advantage to a neoplastic cell in the microenvironment of the tissue in which the cancer arises, leading to clonal expansion of cells carrying cancer driver mutations (CDMs) (Figure 1) (Stratton et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation